At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
x=2at/(1+t²)
dx/dt =[(1+t²)(2at)'-(2at)(1+t²)']/(1+t²)²
dx/dt=[(1+t²)(2a)-(2at)(2t)]/(1+t²)²
dx/dt=[2a+2at²-4at²]/(1+t²)²
dx/dt=[2a-2at²]/(1+t²)²
y=[b(1-t²)]/(1+t²)
dy/dt=[(1+t²)(b(1-t²))'-b(1-t²)(1+t²)']/(1+t²)²
dy/dt=[((1+t²)(-2bt)-b(1-t²)(2t)]/(1+t²)²
dy/dt=(-2bt-2bt³-2bt+2bt³)/(1+t²)²
dy/dt=(-4bt)/(1+t²)²
dy/dx=(dy/dt)/(dx/dt)
dy/dx=[(-4bt)/(1+t²)²]/[(2a-2at²)/(1+t²)²]
Cancelling common denominator
dy/dx=(-4bt)/(2a-2at²)
dy/dx=(-2bt)/(a-at²)
dy/dx=(2bt)/(at²-a)
Differentiating the above equation
y''=d²y/dx²=D[(2bt)/(at²-a)]
y''=[(at²-a)D(2bt)-(2bt)D(at²-a)]/(at²-a)²
y''=[(at²-a)(2b)(dt/dx)-(2bt)(2at)(dt/dx)]/(at²-a)²
dt/dx=(1+t²)²/(2a-2at²)
y''=[(at²-a)(2b)[(1+t²)²/(2a(1-t²))]-
(4abt²)[(1+t²)²/(2a-2at²)]/(at²-a)²
y''=[(-b)(1+t²)²-(2bt²)[(1+t²)²/(1-t²)]/(at²-a)²
y''=[(-b)(1+t²)²(1-t²)-(2bt²)(1+t²)²]/[(1-t²)(at²-a)²]
y''=[b(1+t²)²(t²-1)-2bt²(1+t²)²]/[(1-t²)(at²-a)²]
Step-by-step explanation:
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.